1985
DOI: 10.1159/000124096
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Hypothalamic Luteinizing Hormone

Abstract: Ultracentrifugation and sucrose gradient separation techniques have been applied to study of the subcellular distribution of hypothalamic luteinizing hormone (LH). Subcellular particle-bound LH accounted for 42% of the total LH while cytoplasm contained 58% of the total immunoassayable LH in these extracts. 70% of particle-bound LH was present in the P2 fraction and most of the particle-associated LH was found in subfractions of P2 rich in synaptosomes but poor in myelin and mitochondria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Each persists in the brain for at least 7 months after hypophysectomy indicating some independence from the anterior pituitary. Data have also been reported relating to the ontogeny [15], subcellular distribution [6,17], secretory control [5,7,9], and possible roles [2] for these brain-based proteins.More recently, a prolactin-like substance has been ident ified in the rodent brain, primarily utilizing immunohisto chemical identification [10,12,13,25,26]. The present study describes biochemical, immunologic, and biologic characterization of this protein from the rat hypothalamus.…”
mentioning
confidence: 99%
“…Each persists in the brain for at least 7 months after hypophysectomy indicating some independence from the anterior pituitary. Data have also been reported relating to the ontogeny [15], subcellular distribution [6,17], secretory control [5,7,9], and possible roles [2] for these brain-based proteins.More recently, a prolactin-like substance has been ident ified in the rodent brain, primarily utilizing immunohisto chemical identification [10,12,13,25,26]. The present study describes biochemical, immunologic, and biologic characterization of this protein from the rat hypothalamus.…”
mentioning
confidence: 99%
“…Several lines of evidence, including long-term (up to 7 months) persistence of LH in the brain following hypophysectomy at levels not significantly different from intact controls also suggests, but does not prove, that some brain LH is made in situ in the brain [7]. Further, study of the subcellular distribution of brain-based LH has shown that it is largely associated with subcellular fractions rich in synaptosomes but poor in myelin and mitochondria [10]. This observation, along with the demonstration that release of LH from hypothalamic slices can be stimulated by potassium-induced depolariza tion [9], supports the idea that brain LH may act as a neuro transmitter or neuromodulator, transsynaptically, in roles hitherto unsuspected and totally separate from its classical assignment as a reproductive hormone of pituitary origin.…”
Section: Discussionmentioning
confidence: 98%
“…Parlow. Details of the methodology used in this laboratory have been previously reported [8][9][10], Rat LH-RP-2 was used to develop the assay standard curves. Protein concentrations were de termined by the method of Waddell \ 19].…”
Section: Methodsmentioning
confidence: 99%
“…Alterna tively, there may be FSH-secreting neurons within the hypothal amus which release FSH and inhibit the release of LHRH either directly, or indirectly via intemeurons. Indeed, there is evidence to suggest the existence of LH-containing neurons within the hypothalamus [21,22], Plasma FSH was statistically unchanged after intraventricu lar injection of saline or 0.5 pg of o-FSH. Following the next higher dose (4 pg), there was a significant, progressive elevation of plasma FSH above the level of the controls throughout the 12 h of experiment.…”
Section: Discussionmentioning
confidence: 99%